Composite carbon-based electrocatalyst, preparation method thereof, membrane electrode and application of membrane electrode
Through the preparation method of composite carbon-based electrocatalyst, the problem of corrosion of the carbon support of the PEMFC catalyst under harsh conditions is solved, and the excellent corrosion resistance and electrocatalytic activity of the catalyst are achieved, cost is reduced and the durability of the fuel cell is improved.
Patent Information
- Application Number
- CN202411986809.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-31
- Publication Date
- 2025-04-08
AI Technical Summary
The existing proton exchange membrane fuel cell (PEMFC) catalyst carbon support is prone to corrosion under harsh conditions, affecting the durability of the fuel cell.
A composite carbon-based electrocatalyst is prepared by mixing contact between mesoporous nanocarbon fibers and nitrogen source, vacuum coating treatment and hydrothermal reaction, and a composite carbon-based electrocatalyst with excellent corrosion resistance and electrocatalytic activity.
This method reduces the load of platinum, reduces costs, improves the corrosion resistance and redox reaction activity of the catalyst, and extends the service life of the fuel cell.
Smart Images

Figure CN119786625A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of catalyst materials, and in particular to a composite carbon-based electrocatalyst and a preparation method thereof, a membrane electrode and applications thereof. Background Art
[0002] Proton exchange membrane fuel cells (PEMFCs) are considered a viable solution to meet many clean energy needs. However, carbon corrosion under harsh PEMFC conditions has not been fully addressed. The high electric fields generated during the start-stop process of the fuel cell and / or fuel starvation lead to electrochemical oxidation corrosion of the carbon support, structural deterioration, and dissolution of the metal catalyst (Pt), which seriously affects the durability of PEMFCs. A good catalyst support should have excellent chemical stability to withstand the harsh environment of PEMFCs, high conductivity for rapid electron transfer, a unique pore structure for efficient transfer of reactants / byproducts, a large surface area to maximize catalyst utilization, and a strong catalyst-support interaction.
[0003] Therefore, in order to ensure the long-term stable operation of PEMFC, it is crucial to develop better corrosion-resistant catalyst carbon supports.
[0004] CN 110010906A discloses a method for preparing a Pt / TiN@CN catalyst with high oxygen reduction activity. The method firstly 4 Steam is used as the raw material of the C carrier, and a TiN@CN carrier with a flaky core-shell structure is obtained by high-temperature calcination. Then a Pt catalyst is loaded on the TiN@CN carrier to obtain a Pt / TiN@CN catalyst. This catalyst increases the specific surface area of the material, better disperses the Pt catalyst, and improves the catalytic activity. However, it has only been characterized in a half-cell, and its performance in the actual application of PEMFCs is unknown. Summary of the invention
[0005] The object of the present invention is to provide a proton exchange membrane fuel cell catalyst having excellent electrocatalytic activity, corrosion resistance and stability.
[0006] In order to achieve the above object, the first aspect of the present invention provides a method for preparing a composite carbon-based electrocatalyst, the method comprising:
[0007] (1) in the presence of a solvent, sequentially drying and calcining the material obtained by contacting and mixing the mesoporous nanocarbon fibers with a nitrogen source to obtain a first solid;
[0008] (2) vacuum coating the first solid with titanium nitride to obtain a second solid; the vacuum coating has a coating thickness of 10-15 nm;
[0009] (3) in the presence of ethylene glycol, at a pH value of 10-13, subjecting the second solid and the platinum source to a hydrothermal reaction to obtain the composite carbon-based electrocatalyst;
[0010] Wherein, relative to 1 g of the mesoporous nano-carbon fiber, the amount of the nitrogen source used is 1-4 g, and the amount of the platinum source used is 60-70 mL.
[0011] The second aspect of the present invention provides a composite carbon-based electrocatalyst prepared by the method described in the first aspect.
[0012] A third aspect of the present invention provides a membrane electrode, which comprises a gas diffusion layer, a proton exchange membrane, and a cathode catalyst layer and an anode catalyst layer supported on the upper and lower surfaces of the proton exchange membrane;
[0013] Wherein, the cathode catalyst layer is formed by a slurry I containing an alcohol solvent, water, a perfluorosulfonic acid polymer I and a composite carbon-based electrocatalyst;
[0014] The composite carbon-based electrocatalyst is the composite carbon-based electrocatalyst described in the second aspect.
[0015] The fourth aspect of the present invention provides the use of the membrane electrode described in the third aspect in a proton exchange membrane fuel cell.
[0016] Through the above technical solution, the present invention has at least the following advantages:
[0017] (1) The method for preparing a composite carbon-based electrocatalyst provided by the present invention reduces the Pt load and reduces the cost.
[0018] (2) The composite carbon-based electrocatalyst prepared by the method for preparing the composite carbon-based electrocatalyst provided by the present invention has excellent corrosion resistance and obvious electrocatalytic activity for the redox reaction (ORR) of proton exchange membrane fuel cells.
[0019] (3) The composite carbon-based electrocatalyst provided by the present invention can be used as the basis of membrane electrode (MEA) to construct an efficient proton exchange membrane fuel cell (PEMFC), thereby improving the initial performance and durability of the proton exchange membrane fuel cell (PEMFC).
[0020] (4) The composite carbon-based electrocatalyst provided by the present invention has uniformly distributed Pt particles with a size of 2-3 nm, which significantly improves the corrosion resistance of carbon and inhibits the degradation of the electrocatalyst.
[0021] (5) The composite carbon-based electrocatalyst provided by the present invention provides a strong metal support interaction for the catalytic layer of the membrane electrode (MEA), thereby improving the activity and stability of the redox reaction (ORR). BRIEF DESCRIPTION OF THE DRAWINGS
[0022] Figure 1 This is a scanning electron microscope (SEM) image of the composite carbon-based electrocatalyst prepared in Example 1 of the present invention. DETAILED DESCRIPTION
[0023] The endpoints and any values of the ranges disclosed in this article are not limited to the precise ranges or values, and these ranges or values should be understood to include values close to these ranges or values. For numerical ranges, the endpoint values of each range, the endpoint values of each range and the individual point values, and the individual point values can be combined with each other to obtain one or more new numerical ranges, which should be considered as specifically disclosed in this article.
[0024] In the present invention, the carbon paper is a carbon fiber composite paper material, which is mainly made of short-cut carbon fibers and has a fiber porous structure, and can establish an effective channel for the conduction of gas and water.
[0025] The perfluorosulfonic acid polymer has a sulfonic acid group (-SO 3 - ) or H-type polymers with sulfonyl fluoride groups (-SO 3 F) of type F polymer.
[0026] In the present invention, 1 mbar = 100 Pa.
[0027] As mentioned above, the first aspect of the present invention provides a method for preparing a composite carbon-based electrocatalyst, the method comprising:
[0028] (1) in the presence of a solvent, sequentially drying and calcining the material obtained by contacting and mixing the mesoporous nanocarbon fibers with a nitrogen source to obtain a first solid;
[0029] (2) vacuum coating the first solid with titanium nitride to obtain a second solid; the vacuum coating has a coating thickness of 10-15 nm;
[0030] (3) in the presence of ethylene glycol, at a pH value of 10-13, subjecting the second solid and the platinum source to a hydrothermal reaction to obtain the composite carbon-based electrocatalyst;
[0031] Wherein, relative to 1 g of the mesoporous nano-carbon fiber, the amount of the nitrogen source used is 1-4 g, and the amount of the platinum source used is 60-70 mL.
[0032] Preferably, in step (1), the solvent is ethanol, and the amount of ethanol used is 20-35 mL relative to 1 g of the mesoporous nano-carbon fiber.
[0033] Preferably, in step (1), the nitrogen source is urea.
[0034] Preferably, in step (1), the conditions of contact mixing I include: temperature of 23-27° C. and time of 1-2 h.
[0035] Preferably, the calcination is carried out in a nitrogen atmosphere.
[0036] Preferably, the calcination conditions include: a temperature of 500-700° C. and a time of 3-4 hours. In this preferred embodiment, the technical solution of the present invention can obtain a composite carbon-based electrocatalyst with higher redox reaction activity and stability.
[0037] Preferably, the vacuum coating treatment time is 1-8 minutes.
[0038] Preferably, in step (2), the conditions of the vacuum coating process include: a background vacuum degree of 2×10 - 2 mbar-7×10 -2 mbar; coating sputtering power is 130-170W; deposition rate is 2-3nm / min.
[0039] Preferably, in step (2), the equipment for vacuum coating treatment is a magnetron sputtering coating equipment; the present invention has no special requirements for the model of the magnetron sputtering coating equipment. The following text of the present invention provides a specific model of magnetron sputtering coating equipment by way of example, which should not be understood by those skilled in the art as a limitation of the present invention.
[0040] Preferably, in step (3), the amount of ethylene glycol used is 20-50 mL relative to 1 g of the mesoporous nano-carbon fiber.
[0041] Preferably, in step (3), the platinum source is H 2 PtCl 6 6H 2 O, and the H 2 PtCl 6 6H 2 The concentration of solute in O is 8-12mmol / L.
[0042] Preferably, in step (3), the conditions of the hydrothermal reaction include: temperature of 110-130° C. and time of 3-4 h.
[0043] According to a preferred embodiment, the mesoporous carbon nanofiber is prepared by a method comprising the following steps:
[0044] S1: in the presence of an organic solvent, polyacrylonitrile and sodium bicarbonate are contacted and mixed ⅠⅠ to obtain a precursor solution;
[0045] S2: electrospinning the precursor solutions in sequence to obtain nanofibers;
[0046] S3: Pre-oxidizing and carbonizing the nanofibers in sequence to obtain the mesoporous nanocarbon fibers.
[0047] Preferably, in step S1, the organic solvent is N,N-dimethylformamide.
[0048] Preferably, in step S1, the weight ratio of the polyacrylonitrile to the sodium bicarbonate is 6-9:1.
[0049] Preferably, in step S1, the amount of the organic solvent used is 12-15 mL relative to 1 g of the polyacrylonitrile.
[0050] Preferably, in step S1, the conditions of contact mixing II include: temperature of 25-60°C and time of 1-2h.
[0051] Preferably, in step S3, the pre-oxidation conditions include: temperature of 300-400°C and time of 1-2h.
[0052] According to a preferred specific embodiment, the pre-oxidation and the carbonization treatment are both carried out in a nitrogen atmosphere.
[0053] Preferably, the carbonization treatment conditions include: a temperature of 800-900° C. and a time of 1-2 h.
[0054] According to a preferred specific embodiment, the method further comprises: in step S3, the product obtained by the carbonization treatment is subjected to surface functionalization treatment and drying in sequence to obtain the mesoporous nano-carbon fiber.
[0055] More preferably, the surface functionalization treatment comprises pickling and water washing; wherein the pickling substance is an acid solution of H 2 SO 4 , concentration is 0.4-0.6mol / L.
[0056] As mentioned above, the second aspect of the present invention provides a composite carbon-based electrocatalyst prepared by the method described in the first aspect.
[0057] As mentioned above, the third aspect of the present invention provides a membrane electrode, which includes a gas diffusion layer, a proton exchange membrane, and a cathode catalyst layer and an anode catalyst layer supported on the upper and lower surfaces of the proton exchange membrane;
[0058] Wherein, the cathode catalyst layer is formed by a slurry I containing an alcohol solvent, water, a perfluorosulfonic acid polymer I and a composite carbon-based electrocatalyst;
[0059] The composite carbon-based electrocatalyst is the composite carbon-based electrocatalyst described in the second aspect.
[0060] Preferably, in the cathode catalyst layer, the loading amount of the composite carbon-based electrocatalyst is 0.3-0.4 mg based on the platinum contained in the composite carbon-based electrocatalyst. Pt / cm 2 .
[0061] Preferably, the anode catalyst layer is formed by a slurry II containing an alcohol solvent, water, a perfluorosulfonic acid polymer II and a Pt / C catalyst; more preferably, the mass ratio of Pt to C in the Pt / C catalyst is 1:3-5.
[0062] Preferably, the alcohol solvent is n-propanol and / or isopropanol, preferably isopropanol.
[0063] According to a preferred embodiment, in the slurry I, the amount of the perfluorosulfonic acid polymer I is 2-3 g relative to 1 g of the composite carbon-based electrocatalyst;
[0064] Relative to 1 g of the composite carbon-based electrocatalyst, the amount of the alcohol solvent used is 10-14 mL, and the amount of the water used is 7-9 mL.
[0065] According to another preferred embodiment, the solid content of the slurry I and the slurry II at 25° C. is independently 5-12 wt %, and the water-to-alcohol ratio is independently 0.7-1.1; wherein the water-to-alcohol ratio refers to the weight ratio of water to alcohol solvent.
[0066] Preferably, in the anode catalyst layer, the loading amount of the Pt / C catalyst is 0.05-0.1 mg based on the platinum contained in the Pt / C catalyst. Pt / cm 2 .
[0067] Preferably, in the slurry Ⅱ, the amount of the perfluorosulfonic acid polymer Ⅱ is 2-3 g relative to 1 g of the Pt / C catalyst.
[0068] Preferably, in the slurry ⅠⅠ, based on the carbon contained in the Pt / C catalyst, the weight ratio of the perfluorosulfonic acid polymer ⅠⅠ to the Pt / C catalyst is 0.5-0.7:1.
[0069] Preferably, the concentrations of the perfluorosulfonic acid polymer I and the perfluorosulfonic acid polymer II are each independently selected from 5-20 wt %.
[0070] Preferably, the gas diffusion layer is carbon paper.
[0071] According to a preferred specific embodiment, the method for preparing the membrane electrode is carried out using the components in the slurry I and the slurry II, comprising:
[0072] T1: coating the slurry I and the slurry Ⅰ on the upper and lower surfaces of the proton exchange membrane respectively to obtain a catalyst coated membrane layer;
[0073] T2: attaching gas diffusion layers to the upper and lower surfaces of the catalyst coated membrane layer respectively to obtain the membrane electrode.
[0074] The present invention has no particular limitation on the coating amount, the coating and the laminating method. Exemplarily, the coating method is spraying or transfer, and the laminating method is hot pressing.
[0075] As mentioned above, the fourth aspect of the present invention provides the use of the membrane electrode described in the third aspect in a proton exchange membrane fuel cell.
[0076] The present invention will be described in detail below by way of examples. In the following examples, unless otherwise specified, the drugs and reagents used are all commercially available products.
[0077] Polyacrylonitrile: purchased from Sigma-Aldrich, CAS No. 25014-41-9, weight average molecular weight M W =150000.
[0078] Perfluorosulfonic acid polymer I and perfluorosulfonic acid polymer Ⅰ: concentration of 20 wt%, purchased from Sigma-Aldrich Company, CAS No. 31175-20-9.
[0079] In the following examples, normal temperature refers to a temperature of 25±2°C.
[0080] In the following examples, the model of the magnetron sputtering coating equipment is NSC-4000(M).
[0081] Preparation Example 1: Preparation of mesoporous carbon nanofibers
[0082] (1) In the presence of 50 mL of an organic solvent (N,N-dimethylformamide), 0.5 g of sodium bicarbonate and 3.5 g of polyacrylonitrile were contacted and mixed ⅠⅠ (temperature: 60° C., time: 1 h) to obtain a precursor solution;
[0083] (2) electrospinning the precursor solution to obtain nanofibers;
[0084] (3) The nanofibers were pre-oxidized (temperature: 320°C, time: 1 h) and carbonized (temperature: 900°C, time: 2 h) in a nitrogen atmosphere;
[0085] Then, 50 mL of 0.5 mol / L acid solution (H 2 SO 4 ) The carbonized product is acid-washed, then washed with deionized water and dried to obtain mesoporous nanocarbon fiber C-1.
[0086] Preparation Example 2
[0087] This preparation example is carried out using a method similar to that of Preparation Example 1, except that the temperature of the carbonization treatment is adjusted to 800°C to obtain mesoporous nanocarbon fiber C-2.
[0088] Example 1: Preparation of composite carbon-based electrocatalyst
[0089] (1) In the presence of 50 mL of solvent (ethanol), 2 g of mesoporous nanocarbon fiber C-1 and 5 g of nitrogen source (urea) were contacted and mixed at room temperature I (1.5 h). The obtained material was dried to evaporate the solvent, and then calcined in a nitrogen atmosphere (temperature of 500 ° C., time of 4 h) to obtain a first solid;
[0090] (2) using a magnetron sputtering coating device to vacuum coat the first solid with titanium nitride to obtain a second solid; the vacuum coating process has a coating thickness of 12.5 nm and a coating time of 5 min;
[0091] The conditions for vacuum coating treatment are: the background vacuum degree is 5×10 -2 mbar; coating sputtering power is 150W; deposition rate is 2.5nm / min;
[0092] (3) In the presence of 50 mL of ethylene glycol, NaOH solution was added to adjust the pH value to 10, and 1 g of the second solid and 128.125 mL of a platinum source (H 2 PtCl 6 6H 2 O, wherein the concentration of the solute is 10 mmol / L) was dispersed for hydrothermal reaction (temperature was 120° C., time was 3 h) to obtain a composite carbon-based electrocatalyst F1.
[0093] Example 2
[0094] This example is carried out using a method similar to that of Example 1, except that the mesoporous carbon nanofiber C-1 is replaced with an equal mass of mesoporous carbon nanofiber C-2 to obtain a composite carbon-based electrocatalyst F2.
[0095] Example 3
[0096] This example is carried out using a method similar to that of Example 1, except that the calcination conditions in this example are adjusted to: temperature of 800° C., time of 4 h, to obtain a composite carbon-based electrocatalyst F3.
[0097] Comparative Example 1
[0098] In this comparative example, a method similar to step (3) in Example 1 was used, and the specific steps of the method are:
[0099] In the presence of 50 mL of ethylene glycol, NaOH solution was added to adjust the pH value to 10, and 1 g of mesoporous nanocarbon fiber C-1 and 128.125 mL of platinum source (H 2 PtCl 6 6H 2 O, wherein the concentration of the solute is 10 mmol / L) is dispersed for hydrothermal reaction (temperature is 120° C., time is 3 h) to obtain a composite carbon-based electrocatalyst, thereby obtaining a composite carbon-based electrocatalyst D1.
[0100] Comparative Example 2
[0101] In this comparative example, a method similar to steps (2) and (3) in Example 1 was used, and the specific steps of the method are:
[0102] (1) using a magnetron sputtering coating device, 2 g of mesoporous nanocarbon fiber C-1 is vacuum coated with titanium nitride to obtain a first solid; the coating thickness of the vacuum coating treatment is 12.5 nm;
[0103] The conditions for vacuum coating treatment are: the background vacuum degree is 5×10 -2 mbar; coating sputtering power is 150W; deposition rate is 2.5nm / min;
[0104] (2) In the presence of 50 mL of ethylene glycol, NaOH solution was added to adjust the pH value to 10, and 1 g of the first solid and 128.125 mL of a platinum source (H 2 PtCl 6 6H 2 O, wherein the concentration of the solute is 10 mmol / L) is dispersed for hydrothermal reaction (temperature is 120°C, time is 3 h) to obtain a composite carbon-based electrocatalyst D2.
[0105] Comparative Example 3
[0106] In this comparative example, a method similar to steps (1) and (3) is used, and the specific steps of the method are:
[0107] (1) In the presence of 50 mL of solvent (ethanol), 2 g of mesoporous nanocarbon fiber C-1 and 5 g of nitrogen source (urea) were contacted and mixed at room temperature I (1.5 h). The obtained material was dried to evaporate the solvent, and then calcined in a nitrogen atmosphere (temperature of 500 ° C., time of 4 h) to obtain a first solid;
[0108] (2) In the presence of 50 mL of ethylene glycol, NaOH solution was added to adjust the pH value to 10, and 1 g of the first solid and 128.125 mL of a platinum source (H 2 PtCl 6 6H 2 O, wherein the concentration of the solute is 10 mmol / L) is dispersed for hydrothermal reaction to obtain a composite carbon-based electrocatalyst D3.
[0109] Application example 1: Preparation of membrane electrode
[0110] (1) At room temperature, 12.83 mL of alcohol solvent (isopropanol), 8.38 mL of deionized water, 2.6 g of perfluorosulfonic acid polymer I and 1 g of composite carbon-based electrocatalyst F1 were mixed to obtain slurry I;
[0111] 12.83 mL of alcohol solvent (isopropanol), 8.38 mL of deionized water, 2.6 g of perfluorosulfonic acid polymer ⅠⅠ and Pt / C catalyst (the mass ratio of Pt to C is 1:4) were mixed to obtain slurry ⅠⅠ;
[0112] The slurry I and slurry ⅠⅠ are coated (sprayed) on the upper and lower surfaces of the proton exchange membrane respectively to obtain a catalyst coated membrane layer;
[0113] (2) laminating the gas diffusion layer (carbon paper) on the upper and lower surfaces of the catalyst coating membrane layer by hot pressing to obtain a membrane electrode M1;
[0114] The weight ratio of the perfluorosulfonic acid polymer ⅠⅠ to the Pt / C catalyst is 0.7:1 based on the carbon contained in the Pt / C catalyst;
[0115] In step (2), the coating amount of slurry I is 0.3 mg / cm2 based on the platinum contained in the composite carbon-based electrocatalyst in slurry I. 2 Based on the platinum contained in the Pt / C catalyst in slurry ⅠⅠ, the coating amount of slurry ⅠⅠ is 0.05mg / cm 2 .
[0116] Application Example 2 to Application Example 3
[0117] The method is similar to that of Application Example 1, except that F1 in Application Example 1 is replaced by F2 and F3, respectively, to obtain membrane electrodes M2 and M3, respectively.
[0118] Comparative Application Example 1 to Comparative Application Example 3
[0119] The method is similar to that of Application Example 1, except that F1 in Application Example 1 is replaced by D1, D2, and D3, respectively, to obtain membrane electrodes DM1, DM2, and DM3, respectively.
[0120] Test Case
[0121] The microstructure of the composite carbon-based electrocatalyst prepared in Example 1 was tested using a scanning electron microscope (SEM) of the SUPRA40 model produced by Carl Zeiss of Germany, and the test condition was 100K.
[0122] All membrane electrodes obtained in the corresponding examples were assembled into single cells and polarization curve tests were performed. 2 / O 2 The single cell test was carried out under a temperature of 75°C, a relative humidity of 100%, and an active area of 25 cm 2 ; At the same time, the membrane electrode assembly (MEA) was activated before testing the polarization curve. The initial electrical performance test results are shown in Table 1, and the electrical performance after durability is shown in Table 2.
[0123] The present invention is exemplarily Figure 1 The scanning electron microscope (SEM) image of the composite carbon-based electrocatalyst prepared in Example 1 is provided. Figure 1 It can be seen that the composite carbon-based electrocatalyst provided in Example 1 has the characteristics of a mesoporous structure and a high specific surface area, N is doped in the catalyst, and Pt nanoparticles are evenly distributed on its surface, which indicates that the composite carbon-based electrocatalyst provided by the present invention has abundant active sites, thereby bringing about a good mass transfer effect.
[0124] Table 1
[0125] Membrane Electrode <![CDATA[Current density (A cm -2 )]]> Voltage (V) <![CDATA[Power density (W cm -2 )]]> M1 2.0 0.661 1.322 M2 2.0 0.655 1.31 M3 2.0 0.658 1.316 DM1 2.0 0.623 1.246 DM2 2.0 0.638 1.276 DM3 2.0 0.645 1.29
[0126] Table 2
[0127] Membrane Electrode <![CDATA[Current density (A cm -2 )]]> Voltage (V) <![CDATA[Power density (W cm -2 )]]> M1 2.0 0.657 1.314 M2 2.0 0.650 1.30 M3 2.0 0.654 1.308 DM1 2.0 0.611 1.222 DM2 2.0 0.628 1.256 DM3 2.0 0.636 1.272
[0128] It can be seen from the above results that the composite carbon-based electrocatalyst prepared by the method for preparing a composite carbon-based electrocatalyst provided by the present invention exhibits excellent electrochemical performance in tests when applied to a single cell assembled with a membrane electrode.
[0129] Among them, after the durability test, the power density of the single cell assembled by the membrane electrode of Application Example 1 only decreased by 0.6%, which shows that the composite carbon-based electrocatalyst provided by the present invention has good antioxidant and corrosion resistance.
[0130] Therefore, the composite carbon-based electrocatalyst provided by the present invention is a typical example of the transformation of the stable developed electrocatalyst material to a durable proton exchange membrane fuel cell (PEMFC).
[0131] The preferred embodiments of the present invention are described in detail above, but the present invention is not limited thereto. Within the technical concept of the present invention, the technical solution of the present invention can be subjected to a variety of simple modifications, including the combination of various technical features in any other suitable manner, and these simple modifications and combinations should also be regarded as the contents disclosed by the present invention and belong to the protection scope of the present invention.
Claims
1. A method for preparing a composite carbon-based electrocatalyst, characterized in that: The method includes: (1) in the presence of a solvent, sequentially drying and calcining the material obtained by contacting and mixing the mesoporous nanocarbon fibers with a nitrogen source to obtain a first solid; (2) vacuum coating the first solid with titanium nitride to obtain a second solid; the vacuum coating has a coating thickness of 10-15 nm; (3) in the presence of ethylene glycol, at a pH value of 10-13, subjecting the second solid and the platinum source to a hydrothermal reaction to obtain the composite carbon-based electrocatalyst; Wherein, relative to 1 g of the mesoporous nano-carbon fiber, the amount of the nitrogen source used is 1-4 g, and the amount of the platinum source used is 60-70 mL.
2. The method according to claim 1, characterized in that In step (1), the conditions of contact mixing I include: temperature of 23-27°C and time of 1-2h; And / or, the calcination conditions include: temperature of 500-700° C. and time of 3-4 hours.
3. The method according to claim 1, characterized in that In step (2), the vacuum coating treatment conditions include: the background vacuum degree is 2×10 -2 mbar-7×10 -2 mbar; coating sputtering power is 130-170W; deposition rate is 2-3nm / min.
4. The method according to any one of claims 1 to 3, characterized in that: In step (3), the platinum source is H2PtCl6·6H2O, and the concentration of the solute in the H2PtCl6·6H2O is 8-12 mmol / L.
5. The method according to any one of claims 1 to 3, characterized in that: The mesoporous carbon nanofiber is prepared by a method comprising the following steps: S1: in the presence of an organic solvent, polyacrylonitrile and sodium bicarbonate are contacted and mixed ⅠⅠ to obtain a precursor solution; S2: electrospinning the precursor solutions in sequence to obtain nanofibers; S3: Pre-oxidizing and carbonizing the nanofibers in sequence to obtain the mesoporous nanocarbon fibers.
6. The method according to claim 5, characterized in that In step S3, the pre-oxidation conditions include: temperature of 300-400°C and time of 1-2h; And / or, the carbonization treatment conditions include: temperature of 800-900° C. and time of 1-2 h.
7. A composite carbon-based electrocatalyst prepared by the method described in any one of claims 1 to 6.
8. A membrane electrode, characterized in that: The membrane electrode comprises a gas diffusion layer, a proton exchange membrane, and a cathode catalyst layer and an anode catalyst layer loaded on the upper and lower surfaces of the proton exchange membrane; Wherein, the cathode catalyst layer is formed by a slurry I containing an alcohol solvent, water, a perfluorosulfonic acid polymer I and a composite carbon-based electrocatalyst; The composite carbon-based electrocatalyst is the composite carbon-based electrocatalyst according to claim 7.
9. The membrane electrode according to claim 8, characterized in that: In the cathode catalyst layer, the loading amount of the composite carbon-based electrocatalyst is 0.3-0.4 mg based on the platinum contained in the composite carbon-based electrocatalyst. Pt / cm 2 .
10. Use of the membrane electrode according to claim 8 or 9 in a proton exchange membrane fuel cell.
Citation Information
Patent Citations
Pt / TiN@CN catalyst with high oxygen reduction activity and preparation method thereof, and application of Pt / TiN@CN catalyst with high oxygen reduction activity
CN110010906A